Immunohistochemical features of some connective tissue components of kidney in mesangiocapillary glomerulonephritis type I and diffuse lupus glomerulonephritis - O. V. Khmara; O. O. Dyadyk (Zaporozhye State Medical University, 2014)
Aim. To study immunohistochemical features of some connective tissue components of kidney in mesangiocapillary glomerulonephritis type I and diffuse lupus glomerulonephritis. Methods and results. The features of some components of connective tissue in kidney biopsies of patients with mesangiocapillary glomerulonephritis type I and diffuse lupus glomerulonephritis were studied using immunohistochemical, morphometrical and statistical methods of data analysis. Conclusion. The peculiarities of vimentin and smooth muscle actin distribution in the glomerular and tubular-interstitial apparatus of kidney during these two conditions were identified that can be used for facilitation of differential diagnostic optimization and prognosis of the disease.